2012
DOI: 10.1590/s1516-05722012000100003
|View full text |Cite
|
Sign up to set email alerts
|

Produção de biomassa, teor e composição do óleo essencial de Mentha x piperita L. em resposta a fontes e doses de nitrogênio

Abstract: RESUMO:A adubação nitrogenada influencia o teor e a qualidade dos óleos essenciais de plantas aromáticas. O objetivo deste trabalho foi avaliar a influência de diferentes fontes e doses de nitrogênio na produção de biomassa e teor do óleo essencial de M. x piperita. O delineamento experimental foi de blocos casualizados em esquema fatorial 2 x 3 (duas fontes de nitrogênio e três doses). A aplicação nitrogenada de cobertura foi realizada 30 dias após o transplante das mudas. O óleo essencial foi extraído pelo p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 13 publications
0
8
0
4
Order By: Relevance
“…Some previous studies on peppermint have also shown a significant increase in biomass and essential oil yield with applied N (Piccaglia et al 1993;Ram et al 2012). In contrast, Deschamps et al (2012) tested several sources and rates of N on peppermint and did not find any increase in biomass and essential oil production and any improvement in oil quality. Nevertheless, N is an important ecological factor influencing crop growth and yield.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Some previous studies on peppermint have also shown a significant increase in biomass and essential oil yield with applied N (Piccaglia et al 1993;Ram et al 2012). In contrast, Deschamps et al (2012) tested several sources and rates of N on peppermint and did not find any increase in biomass and essential oil production and any improvement in oil quality. Nevertheless, N is an important ecological factor influencing crop growth and yield.…”
Section: Discussionmentioning
confidence: 70%
“…Peppermint is an important aromatic and medicinal plant used across the world in pharmaceutical, cosmetic and food industries. Its most abundant and valuable constituent is menthol (Deschamps et al 2012). There are a large number of everyday products containing peppermint, such as toothpastes, mouthwashes, chewing gums, peppermint candies, shampoos, soaps and skin care products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found an oil yield equivalent to 3.0 g m -2 , higher than the present study. Deschamps et al (2012), states that the largest amount of essential oil for Mentha x piperita L., is between 60 and 120 days.…”
Section: Discussionmentioning
confidence: 99%
“…Mentha spicata, conhecidas como hortelã ou menta, apresenta relevante importância econômica devido ao mentol, geralmente o constituinte majoritário do seu óleo essencial, com demanda global anual acima de 7000 toneladas [1]. A aplicação das plantas deste gênero como alimentos, medicamentos, especiarias e agentes aromatizantes é bem conhecida, sendo estes usos proporcionados pelo seu óleo essencial [2].…”
Section: Introductionunclassified